Determinants of root‐associated fungal communities within Asteraceae in a semi‐arid grassland. (11th December 2013) - Wehner, Jeannine; Powell, Jeff R.; Muller, Ludo A. H.; Caruso, Tancredi; Veresoglou, Stavros D.; Hempel, Stefan; Rillig, Matthias C.; van der, Marcel
Summary While plant–fungal interactions are important determinants of plant community assembly and ecosystem functioning, the processes underlying fungal community composition are poorly understood. Here, we studied for the first time the root‐associated eumycotan communities in a set of co‐occurring plant species of varying relatedness in a species‐rich, semi‐arid grassland in Germany. The study system provides an opportunity to evaluate the importance of host plants and gradients in soil type and landscape structure as drivers of fungal community structure on a relevant spatial scale. We used 454 pyrosequencing of the fungal internal transcribed spacer region to analyse root‐associated eumycotan communities of 25 species within the Asteraceae, which were sampled at different locations within a soil type gradient. We partitioned the variance accounted for by three predictors (host plant phylogeny, spatial distribution and soil type) to quantify their relative roles in determining fungal community composition and used null model analyses to determine whether community composition was influenced by biotic interactions among the fungi. We found a high fungal diversity (156 816 sequences clustered in 1100 operational taxonomic units (OTUs)). Most OTUs belonged to the phylum Ascomycota (35.8%); the most abundant phylotype best‐matched Phialophora mustea. Basidiomycota were represented by 18.3%, with Sebacina as most abundant genus. The three predictors explained 30% of variation in the community structure of root‐associated fungi, with host plant phylogeny being the most important variance component. Null model analysis suggested that many fungal taxa co‐occurred less often than expected by chance, which demonstrates spatial segregation and indicates that negative interactions may prevail in the assembly of fungal communities. Synthesis. The results show that the phylogenetic relationship of host plants is the most important predictor of root‐associated fungal community assembly, indicating that fungal colonization of host plants might be facilitated by certain plant traits that may be shared among closely related plant species.